Measuring Explicit Prejudice and Transphobia in Nursing Students and Professionals - Jesús Manuel García-Acosta; María Elisa Castro-Peraza; Lilisbeth Perestelo-Pérez; Amado Rivero-Santana; Ángeles Arias-Rodríguez; Nieves Doria Lorenzo-Rocha (MDPI AG, 2020)
Trans* people frequently report attitudes of prejudice/transphobia in health professionals. Conversely, health professionals indicate the lack of adequate training to care for these people and its impact on the quality of care provided. Objective: Our objective was to evaluate the explicit prejudices/transphobia of health students and professionals and compare them with the general population in Tenerife. Methods: A descriptive cross-sectional study was carried out with the Genderism and Transphobia Scale (GTS) and the Negative Attitude towards Trans* people Scale (EANT) with a total of 602 participants. Results: We found a low mean level of explicit prejudice/transphobia, with little/no differences between occupation groups. Explicit transphobia was correlated with being a man, less educated, and heterosexual, and not personally knowing a trans* person. Men and women were less transphobic about trans* people whose identities coincided with their own. Conclusion: All participants showed a low mean level of explicit transphobia. This result is not incompatible with unconscious prejudice, which may translate to discriminatory behaviors. Interventions to change negative attitudes are still needed, since even a small percentage of transphobic health professionals could exert a considerable negative impact on health care. In professionals without transphobic attitudes, the barriers identified by trans* people might be a problem due to the lack of specific training.